A Colorado Front Range grassland exhibits decreasing dominance of cheatgrass (Bromus tectorum) over time - Janet S. Prevéy; Timothy R. Seastedt (Ecosphere)
Abstract Causes, consequences, and potentials for recovery from invasions by the invasive annual grass, cheatgrass (Bromus tectorum), in western North America have been extensively documented. The vast majority of these studies have come from regions where yearly precipitation is dominated by “winter‐wet” patterns, but this species has also demonstrated its ability to invade plant communities in “spring/summer‐wet” areas as well. In grasslands of the Front Range of Colorado, a region experiencing a “spring/summer‐wet” precipitation pattern, cheatgrass can exploit early‐season soil moisture, but moderate rainfall continues into the growing season beyond the time of cheatgrass senescence. In this study, we measured how cheatgrass dominance changed over a 13‐year interval in a disturbed meadow along the Front Range of Colorado with a “spring/summer‐wet” precipitation pattern. Cheatgrass cover declined in absolute abundance by about 50% while total vegetation cover increased over this time period. The site was neither grazed nor burned during this interval. A “spring/summer‐wet” precipitation pattern with high interannual variation in amounts occurred during the study, but no relationships between the seasonality or amounts of precipitation and the directional decline in cheatgrass abundance were observed. Rainout shelter manipulations showed that the seasonality of precipitation influenced cheatgrass abundance, with winter drought treatments reducing cheatgrass cover relative to plots that experienced summer drought treatments. The cheatgrass decline corresponded with a lesser decline in native grass cover and no change in native forb cover, while the abundance of non‐native perennial grasses and forb species increased over the study interval. Although cheatgrass can invade communities across broad climatic gradients following disturbance, results from this study show that the persistence of cheatgrass within invaded areas may depend on the seasonality of precipitation and plant communities that vary across these gradients.